A Preliminary Review of Service Design for Repair Practices - Apostolova, Viktoria Yuliyeva; Simeone, Luca; Laursen, Linda Nhu (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Repair remains an underutilised strategy in the circular economy, often deprioritised in favor of recycling despite its potential to reduce environmental impact and extend product lifespans (Keulemans et al., 2023). This systematic literature review investigates how service design can be leveraged to strengthen repair practices. By analysing 60 studies, three key levels of intervention emerge: (1) the micro level, where service design can influence consumer engagement, producer-user interactions, and repair motivations; (2) the meso level, focusing on tools, digital platforms, and process frameworks that facilitate repair accessibility and efficiency; and (3) the macro level, where service design has the potential to shape regulatory frameworks, business models, and cultural shifts that embed repair as a societal norm. Despite its potential, repair is hindered by challenges, such as product complexity (Owen et al., 2024) and insufficient legislative support (Cole & Gnanapragasam, 2017). This review highlights the role of service design in overcoming these barriers by fostering co-creation, developing repair-focused services, and integrating repair into broader sustainability initiatives (Rubenis, 2023). By positioning repair as a service rather than an afterthought, service design could offer new possibilities for circularity and resource efficiency.